Power-generating and transforming equipment for non-conventional energy - International Trade Centre UNCTAD/GATT. (Geneva : International Trade Centre UNCTAD/GATT, 1986)
The study give comments and data on world energy supply, world market for power generating equipment; technologies for solar, wind, biomas, small-hydropower and other forms of non-conventional energy; production of and international trade in non-conventional energy equipment
Vol.1
Includes bibliographical references.
osc 26/03/2019
Loans
Keywords: Electric generator industry; Electric transformer industry; Renewable energy sources